Interrogatory Creedal "Formulae" in Early Egyptian Baptismal Rites: A Reassessment of the Evidence - Johnson, Maxwell E. (Questions liturgiques, 2021)
In response to Alistair Stewart, who has argued that that the current scholarly consensus about creedal formulae in Egypt as originally consisting of a question and answer format at baptism, and not a declaratory creed, is "found wanting", and that any conformity between Egyptian and western baptismal sources is inaccurate, this essay provides a reassessment of the Egyptian evidence. Stewart's use of the current Coptic Rite of Baptism as the key to interpreting earlier sources (Origen, Dionysius, Rufinus, Didymus the Blind, the Canons of Hippolytus, and Cyril of Alexandria) reflects an anachronistic methodological approach. What is consistent and clear in all of these sources is explicit reference to baptismal interrogations and responses. Hence, there is no compelling reason to abandon the scholarly consensus on Alexandrian baptismal creedal formulae